Unsafe Space The Crisis of Free Speech on Campus - Slater, Tom (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
The academy is in crisis. Students call for speakers to be banned, books to be slapped with trigger warnings and university to be a Safe Space, free of offensive words or upsetting ideas. But as tempting as it is to write off intolerant students as a generational blip, or a science experiment gone wrong, they've been getting their ideas from somewhere. Bringing together leading journalists, academics and agitators from the US and UK, Unsafe Space is a wake-up call. From the war on lad culture to the clampdown on climate sceptics, we need to resist all attempts to curtail free speech on campus. But society also needs to take a long, hard look at itself. Our inability to stick up for our founding, liberal values, to insist that the free exchange of ideas should always be a risky business, has eroded free speech from within. Tom Slater is deputy editor at spiked, UK. He coordinates spiked's free-speech campaigns Down With Campus Censorship! and the Free Speech University Rankings, the UK's first university league table for free speech. Tom has written on politics, pop culture and free speech for the Spectator, the Telegraph, Times Higher Education, The Times and the Independent.